2010
DOI: 10.1021/nl1026452
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Structure, Symmetry, and Surface-Inhibited Rotation of Polyoxometalate Ions on Graphene Oxide

Abstract: Atomic-resolution imaging of discrete [γ-SiW10O36]8- lacunary Keggin ions dispersed onto monolayer graphene oxide (GO) films by low voltage aberration corrected transmission electron microscopy is described. Under low electron beam dose, individual anions remain stationary for long enough that a variety of projections can be observed and structural information extracted with ca. ± 0.03 nm precision. Unambiguous assignment of the orientation of individual ions with respect to the point symmetry elements can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…However, the tumbling motion of the nanoclusters can be beneficial for understanding their 3D structures in HRTEM analysis, as a rotating nanocluster allows direct visualisation of all of its principal projections by time-series imaging of the same cluster within the nanotube (Fig 2b-f) without any need to tilt the specimen. Extensive AC-HRTEM image acquisition combined with structural modelling and HRTEM image simulations (Supporting Information file) strongly indicate a highly symmetrical octahedral arrangement of metal atoms with eight  3 -I bridging I-atoms capping each face of the octahedron, and a further six  1 -I atoms coordinated to each metal (Fig 2h-k), yielding a shape topologically similar to polyoxometalate (POM) clusters [31,32] and an overall stoichiometry M6I14 agreeing well with the EDX elemental analysis. The new set of low-frequency Raman bands in the 50 130 cm -1 range emerging as a result of polyiodide and metal complex reaction in SWNT is consistent with the anionic form of the clusters [W6I14] 2- (Fig 2l) and [Mo6I14] 2- (Fig 3k), whereas the G-band is significantly blue-shifted for both clusters with respect to empty nanotubes (Fig 2m and 2j), suggesting that the electrons abstracted from SWNT by iodine in the first step of the inorganic synthesis have been passed onto the metal iodide nanocluster such that the host-nanotube remains positively charged, and the overall structure being described as n·[M6I14] 2-@SWNT 2n+ (Fig 1c).…”
mentioning
confidence: 99%
“…However, the tumbling motion of the nanoclusters can be beneficial for understanding their 3D structures in HRTEM analysis, as a rotating nanocluster allows direct visualisation of all of its principal projections by time-series imaging of the same cluster within the nanotube (Fig 2b-f) without any need to tilt the specimen. Extensive AC-HRTEM image acquisition combined with structural modelling and HRTEM image simulations (Supporting Information file) strongly indicate a highly symmetrical octahedral arrangement of metal atoms with eight  3 -I bridging I-atoms capping each face of the octahedron, and a further six  1 -I atoms coordinated to each metal (Fig 2h-k), yielding a shape topologically similar to polyoxometalate (POM) clusters [31,32] and an overall stoichiometry M6I14 agreeing well with the EDX elemental analysis. The new set of low-frequency Raman bands in the 50 130 cm -1 range emerging as a result of polyiodide and metal complex reaction in SWNT is consistent with the anionic form of the clusters [W6I14] 2- (Fig 2l) and [Mo6I14] 2- (Fig 3k), whereas the G-band is significantly blue-shifted for both clusters with respect to empty nanotubes (Fig 2m and 2j), suggesting that the electrons abstracted from SWNT by iodine in the first step of the inorganic synthesis have been passed onto the metal iodide nanocluster such that the host-nanotube remains positively charged, and the overall structure being described as n·[M6I14] 2-@SWNT 2n+ (Fig 1c).…”
mentioning
confidence: 99%
“…Thei nhibited rotation is caused by interaction with the electron beam and is indicative of as et of metastable orientations.P rior work has observed similar electron beam induced molecular motion on graphene oxide, [32] on carbon nanotubes, [33,34] and for molecules attached to carbon nanohorns,where it was shown that lower acceleration voltages in the TEM resulted in higher frequency of molecular motion as aresult of alarger scattering cross-section. [35,36] An accelerat- Figure 2.…”
Section: Methodsmentioning
confidence: 80%
“…Fig. 1(b) shows a wider field of view image of two parallel DWNTs, one empty, one containing a discrete [W 6 O 19 ] 2-anion. Comparison of a detail of the same structure anion as imaged using the 300 kV HR-TEM (C s = 0.6 mm) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present context, they provide molecular-scale heavy atom motifs with observable symmetry than can be imaged by conventional high resolution transmission electron microscopy (HRTEM) when mounted in single or double walled carbon nanotubes (i.e. SWNTs or DWNTs) or graphene oxide [5,6] 2-ion in DWNTs [5] ( Fig. 1(a)) by HR-TEM and have imaged the W 2 -W 2 atom column separations in the equatorial plane of the anion.…”
Section: Introductionmentioning
confidence: 98%